Development Challenges Of Fruıt And Vegetable Sector Of Uzbekıstan - Tursunbekovich, Iskandarov Sanjarbek (European Scientific Journal, ESJ, 2016)
This article presents development challenges of vegetable and fruit production sector in Uzbekistan. The governmental sector reforms, labour resources, price formation, import and export activities have been the object of the study in this article. The paper reviews several problems with developed support system and further development of fruit and vegetable production in Uzbekistan. The paper is aimed to describe the main problems and challenges and suggest their possible solutions.